การรับรู้ ทัศนคติ และพฤติกรรมของผู้บริโภคที่มีต่อการใช้บริการตลาดเสมือน - รทิตา ไกรเทพ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This research aims to study consumers’ perception, attitude and behavior on the use of a virtual market as well as the relation of consumers’ perception, attitude and behavior. The research methodology is quantitative survey research from 400 samples. The survey was conducted mainly in Bangkok. Data is analyzed by Pearson’s product moment correlation coefficient and linear regression analysis.The findings are as following: 1. the majority of respondent were female with the age between 20-30 years old (Gen C). Most of the respondents had an undergraduate degree. The average income of the respondents was lower 15,000 baht. Most of the respondents were college student. Top 3 products and service according to respondents’ level of perception and interest are clothes, cosmetics and skin care. Electric appliances gain lowest level of interest from respondents.2. Most of the respondents had positive attitude toward a virtual market.3. No significant correlation was shown between and attitude toward a virtual market.4. Positive and significant correlation was found between perception toward a virtual market and behavior on the use of a virtual market.5. Positive and significant correlation was found between attitude toward a virtual market and behavior on the use of a virtual market.6. Perception and attitude toward a virtual market could be used to explain together 25.8 percent of overall factors influencing behavior on the use of a virtual market.